The effects of different light periods on sonic production characteristics of pheasants (p.colchicus) - C Sadettin C; Tepeli; O. Çetin; K. Kırıkçı; K. Yapar; R. Yılmaz (Eurasian Journal of Veterinary Sciences)
This study has been conducted to investigate the effects ol exposing pheasants to different light periods on their egg production characteristics and hatching traits. The daily light period was increased from 11 h light (L): 14 h darkness (□) iniiially to 16 h L. 8 h D in group 1, Birds were exposed lo 16 h L: 8 h D and 8hL:8hD:8hL periods in groups 2 and 3 respectively. Following the onset of stimulatory light, the first egg was obtained in 23 and 22 days in groups 1.2 and 3 respectively, Egg production periods of pheasants were determined as 138 and 136 days in groups 1.2 and 3. Egg yields of pheasants in groups were found as 40 28. 56.57 and 87,68 egg/pheasanl respectively |P<0.05). Average values ol hatchability. fertility and hatchabilily of lertil eggs were determined as 39.48. 48,40 and 54.09 %(P<0.05); 62.17. 68.15 and 70.47% (P<0.05): 63,50. 71,01 and 76.76 % (P<0.05) in groups respectively.